The Effect of Shallot Bulbs Storage Duration and Paclobutrazol Treatments to Disease Attacks on Shallot Plant in Karo Highlands - Rasiska Tarigan; Fatiani Manik; Susilawati Barus (Department of Crop Science, Faculty of Agriculture, Andalas University, 2019)
A major challenge in the development of shallot seeds is the limited availability of qualified seed due to pathogen infection during the vegetative phase. The study aims to determine the effect of storage duration and paclobutrazol (PBZ) treatment to the resistance of shallots crop. The study was conducted at the Berastagi Experimental Fields, Vegetable Crops Research Institute in February to May 2017. The experiment was arranged by randomized block design with two factors. The first factor is bulbs storage duration, which is without storage and stored for 2 months. The second factor is PBZ treatment with levels ie 0, 0.5. 1, 1.5 and 2 mL/L. The observation parameters are the diseases percentage, diseases intensity, roots number, and roots length. The results showed that the shallot bulbs that singly stored had a significant effect on the diseases caused by Peronospora destructor, Alternaria porri, and Fusarium wilt with low percentage category. The PBZ treatment had not significant effect on all observation variables, but the interaction with 2 months storage duration had effect on root length at 60 days after planting (DAP).